Intra-regional trade facilitation: A comparative analysis between ECCAS and ECOWAS - NGUENKWE, Bertrand Ronie; TCHITCHOUA, Jean (Turkish Economic Review, 2019)
Abstract. Since the advent of the Abuja Treaty, Economic Community of Central African States (ECCAS) recorded poor intra-regional trade performance while Economic Community of West African States (ECWAS) performed better. The objective of this paper is to comparatively analyse the impact of trade facilitation measures on intra-regional trade between those two Communities, focusing on the role of Information and Communication Technology and custom environment indicators. Using data from United Nations Conference on Trade and Development, Geodist of Centre d’Etudes Prospectives et d’Informations Internationales and World Bank, our augmented gravity model results showed that internet has a positive and significant impact on the intra-ECCAS trade and no impact on intra-ECOWAS trade. Mobile phone has a positive and significant impact on the intra-regional trade in both zones. The number of days for export has a negative and significant impact on intra-regional trade in both zones, while the result of the number of document is ambiguous. The impact of the increase in these two indicators reduced trade more in ECCAS than in ECOWAS. Keywords. Trade facilitation, ICT, ECCAS, ECOWAS, Augmented gravity model. JEL. C23, H54, O24, R58.